THE RATIO LEGIS LIABILITIES AND REPUDIATION RIGHTS OF LAND DEED OFFICERS BASED ON CRIMINAL CODE PERSPECTIVES - Fachria; Prawesthi, Wahyu (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2023)
Land deed officers have existed as public servants for less time than the notary institution, which extends back more than three centuries. If we take a look at the Basic Agrarian Law included in Law No. 5/1960, we can see that it does not specify the specific responsibilities of Land Deed Officers while creating land deeds. The objective of this research is to analyze a comprehensive overview of the professional practice of land deed officials, who assume that the obligation to register land is upheld in addition to elevating the status of land from conventional rights, in which evidence of ownership is indicated by Petok D, Girik, or Letter C, as well as legal actions related to the acquisition, transfer, and deletion. The method employed in this research is a normative juridical method, and it includes the using legislation, conceptual, historical, and systems approaches as well as literature or law found in books. When land deed officers are requested to testify in civil proceedings, particularly in criminal cases, the repudiation rights of land deed officers that have been established in this legislation and regulation have various problems in their implementation. However, it should be remembered that repudiation rights are "rights" not obligations. Deed of land deed officers who contain legal defects either due to land deed officers' mistakes, negligence, or due to the intention of the land deed officers themselves, the land deed officers must be able to provide accountability both morally and legally.